2015
DOI: 10.1182/blood-2014-06-581793
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic activity of multiple common γ-chain cytokine inhibition in acute and chronic GVHD

Abstract: Key Points• Monoclonal antibody blockade of the common g chain attenuates acute and chronic GVHD.• Common g-chain cytokines increase granzyme B levels in CD8 T cells, which are reduced upon CD132 blockade in vivo.The common g chain (CD132) is a subunit of the interleukin (IL) receptors for IL-2, IL-4, IL-7, IL-9, IL-15, and IL-21. Because levels of several of these cytokines were shown to be increased in the serum of patients developing acute and chronic graft-versus-host disease (GVHD), we reasoned that inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 50 publications
0
54
0
1
Order By: Relevance
“…There is mounting evidence that these 3 cytokines have important roles in cGVHD, transplantation, and autoimmunity. 7,[37][38][39] We also showed that KD025 treatment decreases the presence of TFH cells in cGVHD patient samples ( Figure 5D). This is supported by a decrease in Bcl6 expression in treated cells (Figure 5E,H).…”
Section: Org Frommentioning
confidence: 81%
“…There is mounting evidence that these 3 cytokines have important roles in cGVHD, transplantation, and autoimmunity. 7,[37][38][39] We also showed that KD025 treatment decreases the presence of TFH cells in cGVHD patient samples ( Figure 5D). This is supported by a decrease in Bcl6 expression in treated cells (Figure 5E,H).…”
Section: Org Frommentioning
confidence: 81%
“…Promising new anti-inflammatory drugs such as p38 mitogen-activated protein (MAP) kinase inhibitors [33], anti-CD132 (mAb) [34] and resolvins [35] have not been studied in BO. However, it is important to note that for future proof of concept studies down regulation of neutrophilic inflammation, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…114,115 Consistent with a link between antibody secretion and fibrosis, mice incapable of producing B cells or that produce B cells incapable of immunoglobulin isotype switching, 26 or that receive agents that either preclude GC formation 29,73,116 or deplete B cells 29,117-119 are unable to induce fibrosis or cGVHD. Thus, although unproven at this point, the interaction of allo-(and/or auto) antibody with tissue macrophages would appear an attractive unifying mechanism driving the aberrant macrophage differentiation and function that culminates in tissue fibrosis during cGVHD.…”
Section: Role Of Macrophages In Cgvhd Pathogenesismentioning
confidence: 99%